Does crackdown on corruption reduce stock price crash risk? Evidence from China - Chen, Yunsen; Xie, Yuan; You, Hong; Zhang, Yanan (Journal of Corporate Finance, 2018)
This study examines whether crackdown on political corruption in China affects future stock price crashes. Using data from corruption-related prosecutions, we find that firms under prosecuted official jurisdictions experience a significant decrease in crash risk after the crackdown. Cross-sectional tests show that results are more pronounced for firms with higher political dependence on governments and for firms with worse information environment. Moreover, channel tests provide direct evidence that crackdown decreases crash risk by reducing political risk and bad news hoarding. Overall, our study offers novel evidence on how crackdown on corruption benefits firms.